Acral lentiginous melanoma: a skin cancer with unfavourable prognostic features. A study of the German central malignant melanoma registry (CMMR) in 2050 patients. (20th December 2017) - Teramoto, Y.; Keim, U.; Gesierich, A.; Schuler, G.; Fiedler, E.; Tüting, T.; Ulrich, C.; Wollina, U.; Hassel, J.C.; Gutzmer, R.; Goerdt, S.; Zouboulis, C.; et al.
Summary: Background: Acral lentiginous melanoma (ALM) is one of the four major subtypes in cutaneous melanoma (CM). Although ALM has a poorer prognosis than other CM subtypes, the prognostic factors associated with ALM have only been verified in small‐sized cohorts because of the low incidence of ALM worldwide. Objectives: To investigate the clinical characteristics of ALM and to evaluate their prognostic values based on a large dataset from the Central Malignant Melanoma Registry (CMMR) of the German Dermatologic Society. Methods: The Kaplan–Meier method was used to estimate the potential influence of clinical and histological parameters on ALM disease‐specific survival (DSS) curves, which were compared using the log‐rank test. A Cox proportional hazards model was used to identify independent prognostic factors for DSS. Results: In total, 2050 patients with ALM were identified from 58 949 patients with CM recorded by the CMMR with follow‐up data. In multivariate analyses, age ( P  = 0·006), ulceration ( P  = 0·013), tumour thickness ( P  < 0·001) and tumour spread ( P  < 0·001) turned out to be significant prognostic factors for DSS in ALM whereas sex, nevus association and level of invasion were not independent factors. Conclusions: ALM has the same prognostic factors as other subtypes of melanoma. Unfavourable prognosis probably derives from the delay in diagnosis in comparison with other melanoma subtypes. Abstract : What's already known about this topic? Acral lentiginous melanoma (ALM) has a poorer prognosis than other cutaneous melanoma subtypes. Several published articles have reported various factors that influence the prognosis in ALM but the results of these studies were based on small‐sized cohorts because of the rarity of ALM. What does this study add? This study investigated prognostic factors in the largest‐ever cohort of patients with ALM documented by the Central Malignant Melanoma Registry of the German Dermatologic Society. Four parameters including age, ulceration, tumour thickness and tumour spread were identified as independent significant prognostic factors for disease‐specific survival in ALM. The present American Joint Committee on Cancer classification is valid for ALM. Respond to this article